FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG KULINER MALAM DI KAWASAN ASIA MEGA MAS CHINA TOWN KOTA MEDAN - ARISMAN PARHUSIP; MONTARIS SILAEN; LASMAN EDDY BACHTIAR (LP2MTBM MAKARIOZ, 2023)
Food business or culinary is a business activity that can create jobs for the community and increase the society revenue which is also in the end increase the economic growth of the regional. Capital and the price of culinary food are the factors that influence culinary traders. The purpose of this study are to know the factors that influences the night culinary traders’ revenue in Medan; to know the efforts of the factors influence the level of night culinary trader’s revenue in Medan (Study case: Medan). The results of the research can be concluded that: Capital has a positive and significant influence on culinary trader revenue at Medan, with t-count of 6.935 and a signification level of 0.000.Price has a positive and significant effect on culinary trader revenue at Medan, with t-count of 4,248 and signification level of 0.000.Culinary business is the most popular business, because it relates to the staple food of the community. In order for the culinary business traders to expand their business is expected by the government by facilitating the provision of capital assistance through cooperation, low interest credit, KUR (People's Business Credit).